Job Rotation as a Learning Mechanism - Ortega, Jaime (Management Science, 2001)
This article analyzes the costs and benefits of job rotation as a mechanism with which the firm can learn about the employees' productivities and the profitability of different jobs or activities. I compare job rotation to an assignment policy where employees specialize in one job along their career. The gains from adopting a job rotation policy are larger when there is more prior uncertainty about employees and activities. I argue that this firm learning theory fits the existing evidence on rotation better than alternative explanations based on employee motivation and employee learning.